Analysis of the Competency Model of Driving Teachers in Improving the Quality of Learning in Junior High Schools in Region 3T (Case in Simeulue Regency) - Valentine Simangunsong, Sonya; Ismail, Ismail; Bahrun, Bahrun; Salfiadis, Salfiadis (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
​Objective: This study aims to analyze the competency model of Driving Teachers in improving the quality of learning at the junior high school level in disadvantaged, frontier, and outermost (3T) areas, especially in Simeulue Regency, Aceh Province. This study focuses on the integration of pedagogical, professional, social, and personality competencies supported by learning leadership and their impact on teacher professionalism and student learning outcomes. Methods: This study used a qualitative approach with a case study design involving 15 participants, including driving teachers, principals, and students from three schools in Simeulue Regency. Data were collected through in-depth interviews, participatory observations, and document analysis. Data were analyzed using Miles and Huberman’s interactive model through the processes of data reduction, data presentation, and conclusion drawing and verification. Results: The results of the study show that the Driving Teacher model can transform the role of teachers from curriculum implementers to reflective, collaborative, and innovative learning leaders. Teachers experience improvements in lesson planning, classroom management, and reflection on learning outcomes, supported by a professional learning community and participatory school leadership. In addition, students’ motivation and engagement increased significantly. Novelty: This study presents an integrative conceptual model of teacher competence that connects reflective pedagogy with learning leadership in the context of limited resources. The results of the study expand the theoretical discourse on educational transformation in the 3T region by placing reflection and collaboration as the main mechanism for improving sustainable learning.​